ANALISIS KAVITASI PADA BANGUNAN MERCU PELIMPAH BENDUNGAN KRUENG SABEE MENGUNAKAN MODEL FISIK SKALA 1:30 - Cut Dwi Refika; Ziana Ziana; Ikhlasul Amal (Jurnal Arsip Rekayasa Sipil dan Perencanaan, 2023)
The spillway as a complementary building for the dam functions to release a volume of water that is not accommodated in the dam during a flood (overtopping). To support the continuity of the function of the dam, a safety factor is needed to avoid the potential failure of the weir construction. One of the safety of dams is safety against hydraulic failure, namely cavitation. This problem is caused by an increase in the water level from the dam which can cause changes in flow characteristics and result in damage to the spillway overpass building. The characteristics of the flow passing through the spillway will depend on the shape and nature of the crest of the overflow itself. The phenomenon of cavitation can be observed from a physical model of the dam. The physical model was designed according to the construction plan for the Krueng Sabee Dam which was carried out at the River and Beach Laboratory of the Faculty of Engineering, Syiah Kuala University with a model scale of 1: 30. The outflow discharge from the crest of the spillway is discharged with return periods of 2, 5, 10, 25, 50, 100  and 1000 years. The Krueng Sabee Dam, which is located in Aceh Jaya Regency, Aceh Province, is a multi-purpose dam. This research aims to study the cavitation that occurs in the spillway crest according to the planning of the Krueng Sabee Dam using a physical model test. The research analysis method used to calculate the cavitation safety value is the calculation of the cavitation index. The cavitation index value is affected by pressure and flow velocity. The results of the analysis show that the cavitation index value at each measurement point is greater than 1. Based on the results of the analysis of the cavitation index, its show that cavitation does not occur in the spillway crest of the Krueng Sabee Dam at all return periods, so there is no need for surface protection of the spillway crest.